Ecosophical trans-formation: asignificant ruptures in the Venezuelan teacher - Milagros Elena Rodriguez (Tópicos Educacionais)
In the present investigation from rhizomes we support the ecosophical transformation as significant ruptures in the emerging Venezuelan teacher, this is the complex objective. We do all of this from the complex transparadigm and the transmethod, rhizomatic deconstruction in planetary decoloniality as a liberating project. The inquiry is framed in the lines of research: transepistemologies of knowledge-knowledge and transcomplex transmethodologies and education-transcomplex transepistemologies. In the reconstruction of the profoundly ecosophical transformation of the teacher as an urgency is the imperative of the onto-epistemological liberation of teachers-researchers in light of the significance of the categories: human condition-teaching-research-feeling-thinking; which means that empowering himself with the greatness of what he is as a decolonized human being and from there understanding his worth and that of the country where he is inserted.